PENGARUH KOMPETENSI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN ADMINISTRASI PERKANTORAN RUMAH SAKIT RK CHARITAS PALEMBANG - Agustina Hanafi; Johan Gunady Ony (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The purpose of this research is to analyze the effect of Competencies and Emotional Intelligence on Job Performance of the office administration’s staff of RK Charity Hospital. The population on this research are all of RK Charity Hospital’s employee, including medical and nonmedical staff. Sample in this research using census method, there is 155 office administration staff. Data Analysis is using SEM that operate by AMOS Ver 20. The result of this research shown that Competencies do not influence the Job Performance of office administration’s staff of RK Charity Hospital. However, Emotional Intelligence gives influence to the Job Performance of office administration’s staff of RK Charity Hospital. The dimensions of Knowledge, Skills, Self Concept, Personal Characteristics, and Motives has a strong relationship with Competencies. The Dimensions of Self Awareness, Self Regulation, Motivation, and Social Skills has a strong relationship with Emotional Intelligence. However, Empathy has no strong relationship with Emotional Intelligence.